LITERASI MEDIA SOSIAL DI SMPN 2 CABANGBUNGIN - Pramudita, Diah Ayu; Primasari, Winda; Faiz Ridlo, Azi (Universitas Islam 45 Bekasi, 2023)
The rapid development of technology and the use of social media among children presents new challenges in forming understanding and healthy behavior in using social media. This research aims to carry out community service in Jayabakti Village, Bekasi Regency with a focus on social media literacy to prevent negative impacts such as peer conflict, cyberbullying, and exposure to hoax information, especially for junior high school students. This activity involves students actively uploading photos/posters and captions that comply with social media ethics. The implementation method is in the form of socialization and training at SMPN 2 Cabangbungin. This is used with the aim of increasing understanding of the benefits and negative impacts of using social media, ethics and manners, as well as content or uploads that are not suitable for children to watch. The results of this activity show that students have become more aware of the impact of social media use and can analyze content better. This activity helps students become smart and responsible social media users.